A feasibility study of producing a peanut oil matrix candidate reference material and its application to support monitoring of aflatoxins statues for public health purposes. (1st December 2018) - Xu, Jiao-Jiao; Chen, Qin; Cai, Zeng-Xuan; Ren, Yi-Ping; Zhao, Yun-Feng; Cheng, Jun; Huang, Bai-Fen
Highlights: The first peanut oil candidate for aflatoxin B and G groups was produced. A feasibility study exhibited suitable homogeneity and (short- and long term) stability. Measurement uncertainty of each analyte was accounted for. This reference material was applied for proficiency test and could be utilized as a quality control standard. Abstract: The first peanut oil reference materials in naturally contaminated aflatoxins was developed, because of the high consumption of this product and the potential risk associated herewith. Based on liquid chromatographic method, homogeneity, short-term of 60 °C for seven days and long-term of 25 °C for twelve months' stability studies of candidates were assessed. The obtained data and statistical results showed a successful feasibility study, without any significant trend. Nine selected expert laboratories were invited to certify the contents of candidates using distinguish quantitative liquid chromatographic method. The certified values and expanded uncertainties ( k  = 2) for these two batches were 6.5 ± 1.6 μg/kg, 29.3 ± 5.3 μg/kg for aflatoxin B1 ; 1.2 ± 0.3 μg/kg, 5.2 ± 0.9 μg/kg for aflatoxin B2 ; 5.0 ± 0.4 μg/kg, 8.4 ± 0.7 μg/kg for aflatoxin G1 ; and 2.1 ± 0.2 μg/kg, 3.5 ± 0.2 μg/kg for aflatoxin G2, respectively.